GAMBARAN KEPATUHAN PENGAMBILAN RESEP ULANG PASIEN DIABETES MILETUS PESERTA PROGRAM RUJUK BALIK (PRB) DI APOTEK MEDIKA (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2021)
Refer Back Program (PRB) is one of BPJS flagship programs to facilitate access to health services to participants with chronic diseases, such as diabetes mellitus. Diabetes Mellitus (DM) cannot be cured, but it is only to reduce the risk of instability. Adherence to taking drugs is classified into three kinds. One of them is not to redeem the recipe (refills not obtained). The purpose of this study was to describe the compliance with re-prescription in diabetes mellitus patients who followed the referral program at Medika Pharmacy. This research was conducted at the Medika Pharmacy. The sampling technique used in this study was purposive sampling, the research instrument used was the Medication Possesion Ratio (MPR) method and the analysis method used data collection sheets to collect data on patient names, names of anti-diabetes mellitus drugs, number of drugs, and date of prescription redemption. The results obtained from the MPR calculation of the number of days the patient should have received the drug and the number of days the patient did not receive the drug was said to be compliant if the percentage value was more than the same as 80% it was said to be disobedient if the percentage value was 80% down. The results of the study showed that the level of adherence to taking drugs from BPJS patients who took part in the Referral Program (PRB) at Apotek Medika was included in the obedient category for a period of 3 months (88,31%) and non-adherent for a period of 6 months (65,63%).